ANALISIS FAKTOR KETERSEDIAAN BERAS DI KABUPATEN CIANJUR TAHUN 2002-2013 - Elpawati Elpawati; Rahmi Purnomowati; Agung Nugraha (JURNAL AGRIBISNIS TERPADU, 2017)
West Java is one of the national rice barn, and Cianjur regency is one of the contributors to rice production in West Java because in Cianjur area there are still many potential rice paddy field and could continue to be developed with the geographical situation and human resources support. Communities in the Cianjur district average as farmers of rice fields. Hereditary profession was handed down from ancestors, although some are switched professions to become factory workers, but there are still people who continue the Cianjur district as farmers continue their ancestral profession. In such circumstances it is the availability of rice will be met, and therefore there needs to be studies focused on the problems of availability of rice in Cianjur. The purpose of this study are: (1). Identify the factors that affect the availability of rice in Cianjur during 2002 - 2013. (2). Analyzing the factors-factors that affect the availability of rice in Cianjur during 2002 - 2013. The study conducted in Cianjur at the time in December 2015 through February 2016. The data used in this research is secondary data based on time series (time series) in 2002 - 2013 by means of multiple linear analysis and analysis in though using SPSS 22. Based on the results and a discussion of factors - factors that affect the availability of rice in Cianjur analyzed in this study are the price of rice, rice field area, the consumption of rice, cassava price and technology. The variables that significantly namely land and technology in the real level (α) of ten percent. The price of rice, cassava price and consumption, each having a t-count value is less than the value of the t-table, the results of these tests indicate that the variable price of rice, cassava price and consumption did not significantly or not significantly affect the availability of rice on significance level (α) of ten percent. While the area of wetland and technology have a t-count value is greater than the value of the t-table. These test results show that the vast variable wetland and technology significant influence or significant effect on the availability of rice on the real level (α) of ten percent.